Contrastive Characterization in Ruth 1:6–22: Three Ways to Return from Exile - Decker, Timothy L (Old Testament Essays, 2019)
By using the narrative device of contrastive characterization, the author of Ruth demonstrates three return-from-exile scenarios that act as a model for the audience. Orpah served as Ruth’s foil and represents a return to the pagan culture. Naomi and Ruth project a role reversal. While Naomi returns more like a pagan than a Jewess, Ruth has demonstrated covenant fidelity and illustrated loyalty to YHWH and Israel. She is thus a model for how Jews ought to return from exile to exodus. https://doi.org/10.17159/2312-3621/2019/v32n3a8